PENGARUH TUNJANGAN KERJA TERHADAP KUALITAS PELAYANAN APARATUR DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA MANADO - SIMON, EMIAZAR; Dengo, Salmin; Pombengi, Jericho (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: This study aims to determine and analyze the effect of job allowances on the quality of service apparatus in the Department of Investment and Integrated Service One Door Manado City. The research method is a quantitative research method, it is a research method based on the philosophy of positivism, used to examine the population or a particular sample. The sampling technique used is a saturated sampling technique in the Department of Investment and Integrated Services One Door Manado City there are 55 ASN. Data analysis techniques used are simple linear regression analysis and simple correlation analysis. Based on the results of analysis using correlation pearson product moment obtained correlation coefficient (r) = 0.566 while the coefficient of determination (rÂ²) = 0.32. These results show that the coefficient of determination is 32%. Based on this result it can be explained that the improvement of service quality of apparatus is 32% while 68% is determined by other factors. Based on this research, the hypothesis presented can be accepted that there is a degree of linkage and determination of the work allowance to the quality of service apparatus in the Department of Investment and Integrated Service One Door Manado City. Based on the results of significance test obtained value tcount = 6.262 at significant level (Î±) = 0.05 with degrees of freedom (df) = n - 2 = 53, then ttable = 2.005. From the data it is obtained that tcount is greater than ttable where tcount 6.262 > 2.005. Then H1 is accepted and H0 is rejected. This proves that there is significant influence between work allowance to service quality of apparatus in the Department of Investment and Integrated Service One Door Manado City. Based on the results of the study, it can be concluded work allowance has a relationship and has a significant effect on the quality of apparatus service in the Department of Investment and Integrated Service One Door Manado City. This means that the work allowance is one of the determinants of the improvement of service quality of the apparatus.Keywords: Work Allowances, Quality of Service Apparatus